Automated leukocyte processing by microfluidic deterministic lateral displacement. Issue 12 (22nd November 2016) - Civin, Curt I.; Ward, Tony; Skelley, Alison M.; Gandhi, Khushroo; Peilun Lee, Zendra; Dosier, Christopher R.; D'Silva, Joseph L.; Chen, Yu; Kim, MinJung; Moynihan, James; Chen, Xiaochun; Aurich, Lee; et al.
Abstract: We previously developed a Deterministic Lateral Displacement (DLD) microfluidic method in silicon to separate cells of various sizes from blood (Davis et al., Proc Natl Acad Sci 2006;103:14779‐14784; Huang et al., Science 2004;304:987‐990). Here, we present the reduction‐to‐practice of this technology with a commercially produced, high precision plastic microfluidic chip‐based device designed for automated preparation of human leukocytes (white blood cells; WBCs) for flow cytometry, without centrifugation or manual handling of samples. After a human blood sample was incubated with fluorochrome‐conjugated monoclonal antibodies (mAbs), the mixture was input to a DLD microfluidic chip (microchip) where it was driven through a micropost array designed to deflect WBCs via DLD on the basis of cell size from the Input flow stream into a buffer stream, thus separating WBCs and any larger cells from smaller cells and particles and washing them simultaneously. We developed a microfluidic cell processing protocol that recovered 88% (average) of input WBCs and removed 99.985% (average) of Input erythrocytes (red blood cells) and >99% of unbound mAb in 18 min (average). Flow cytometric evaluation of the microchip Product, with no further processing, lysis or centrifugation, revealed excellent forward and side light scattering and fluorescence characteristics of immunolabeled WBCs. These results indicate that cost‐effective plastic DLD microchips can speed and automate leukocyte processing for high quality flow cytometry analysis, and suggest their utility for multiple other research and clinical applications involving enrichment or depletion of common or rare cell types from blood or tissue samples. © 2016 International Society for Advancement of Cytometry